2017
DOI: 10.1111/jfpp.13441
|View full text |Cite
|
Sign up to set email alerts
|

The use of orange peel essential oil microemulsion and nanoemulsion in pectin‐based coating to extend the shelf life of fresh‐cut orange

Abstract: This study was conducted to evaluate the effect of pectin‐based edible coatings containing orange peel essential oil (OPEO) at 0.5 and 1.0% concentrations on quality parameters of orange slices stored at 4 °C for 17 days. The variations of pH and titratable acidity in coated samples containing microemulsion and nanoemulsion were significantly higher than the controls and pectin‐coated slices. The highest and lowest increases of the total soluble solids were observed in controls and 1% OPEO nanoemulsion samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 35 publications
2
57
0
4
Order By: Relevance
“…Organic acids including citric and malic acids are the main substrates of respiration; thus, reduction of acidity happens in respiring fruit . The decrease in TA during storage has been previously observed on coated citric fruits . The preservation of TA in coated fruit compared with the control sample indicated that the polysaccharide based coatings retarded ripening by creating a semi‐permeable barrier around the fruit …”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Organic acids including citric and malic acids are the main substrates of respiration; thus, reduction of acidity happens in respiring fruit . The decrease in TA during storage has been previously observed on coated citric fruits . The preservation of TA in coated fruit compared with the control sample indicated that the polysaccharide based coatings retarded ripening by creating a semi‐permeable barrier around the fruit …”
Section: Resultssupporting
confidence: 56%
“…Upon removal from storage at 5 °C, TA in non‐coated fruit was lower than the treated fruit, but with storing an additional week at 20 °C, there was no significant difference in TA of fruit regardless of the coating type. The lower TA level in uncoated oranges link to the organic acid decrease because of the increase in respiration rate throughout storage . Organic acids including citric and malic acids are the main substrates of respiration; thus, reduction of acidity happens in respiring fruit .…”
Section: Resultsmentioning
confidence: 98%
“…Caseinate coatings containing ginger essential oil nanoemulsion inhibited bacteria on refrigerated chicken fillets, when compared to uncoated fillets or those with a control coating, and nanoemulsions demonstrated better performance than regular emulsions . Similarly, pectin coatings with orange peel essential oil nanoemulsion were more effective to extend stability of orange slices than the corresponding films with microemulsions, without negative impacts on sensory attributes . Quinoa protein/chitosan coatings containing thymol nanoemulsion were more effective than a regular coating to inhibit fungal decay of strawberries .…”
Section: Nanocarriers For Antimicrobial Agentsmentioning
confidence: 93%
“…[126] Similarly, pectin coatings with orange peel essential oil nanoemulsion were more effective to extend stability of orange slices than the corresponding films with microemulsions, without negative impacts on sensory attributes. [127] Quinoa protein/chitosan coatings containing thymol nanoemulsion were more effective than a regular coating to inhibit fungal decay of strawberries. [128] Similarly, the fungal decay of okra pods was inhibited by an alginate coating containing basil oil nanoemulsion.…”
Section: Nanoemulsionsmentioning
confidence: 99%
“…NE-based edible coatings containing oregano EO and mandarin fiber were found to improve the shelf life of low-fat cut cheese (Artiga-Artigas et al 2017). Orange peel EO (0.5 and 1.0%) ME and NE used in pectin-based coating to extend the shelf life of fresh-cut orange, maintained at 4 °C for 17days, notably reduced weight and ascorbic acid losses of coated samples as well as higher antibacterial and antifungal effects were estimated compared to control without changes in senzory parameters (Radi et al 2018). Taghavi et al (2018) investigated the effects of the microfluidic pressure (600−1200 bar) and cycles (2−4) on the inhibitory activity and physicochemical properties of the NE loaded with a natural antibacterial mixture (i.e., citral, trans-2-hexen-1-ol, and linalool, 1:1:1 w/w) and found that in general the physicochemical properties of the antibacterial NE were affected by the cycle to greater extent than by the pressure and the microfluidization condition did not considerably affect the antibacterial activity of the NE.…”
Section: Nanoemulsions Used In Edible Coatingsmentioning
confidence: 99%